EMPHATY AND TOLERANCE IN PHYSICAL EDUCATION: COOPERATIVE VS. CLASSICAL LEARNING - Sri Winarni; Rusli Rutan (Jurnal Cakrawala Pendidikan, 2020)
There is a common belief that physical education is potential to introduce moral values, such as emphaty and tolerance. However, belief itself is still debatable and needs more empirical evidence. This study aimed to examine the effectiveness of two learning methods commonly used in physical education, these are cooperative and classical learning, whether it could be used for learning the moral values. There were 128 eight graders (52 boys and 76 girls) involved in the experiment. These students were categorised as above average in academic, diversed in religion and social economy background, but they are mostly Javanese. The emphaty was measured using Baron-Cohen scale, while the tolerance was measured using the instrument developed by UNESCO. Using a 2x2 factorial design varying learning model (cooperative vs. classical) and academic achievement (international class vs. regular class). The results showed that cooperative learning was significantly more effective than classical learning. It was found that the emphaty and tolerant scores of the leading class was significantly higher than those in the reguler class. It might be said that those with high cognitive ability may also develop moral values. Nevertheless, no interaction effect was found. This results are discussed using the perspective of socio-constructivism.